2003
DOI: 10.1046/j.1365-2311.2003.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Gall size determines the structure of theRabdophaga strobiloideshost–parasitoid community

Abstract: Abstract.  1. The relationship between gall size and mortality of the willow pinecone gall midge Rabdophaga strobiloides (Diptera: Cecidomyiidae) was examined by determining the fate of all galls in a 30‐ha area in central Alberta, Canada over 4 years. It was found that gall size has a large effect on the type and intensity of mortality experienced by the gall midge, and consequently this factor has the potential to influence the dynamics of the host–parasitoid interaction through the creation of phenotypic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
2
20
1
Order By: Relevance
“…Thus, competition by stemborers can cause a shift in the guild composition of the gall parasitoids, despite not changing parasitism rates overall. Although previous studies have shown variation in galler mortality components consistent with variation in gall size (van Hezewijk & Roland, ), we believe this to be one of the first demonstrations of competition from one guild of phytophagous insects resulting in an alteration of the parasitoid guild structure of another phytophagous species, mediated by host plant and by affecting gall size. The importance of accounting for plant‐trait‐mediated non‐trophic and indirect interactions has been emphasized by Ohgushi (), who demonstrated that including such interactions, which are common in natural communities and sometimes more common than direct trophic interactions, is essential for a complete understanding of factors affecting community composition and assembly.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, competition by stemborers can cause a shift in the guild composition of the gall parasitoids, despite not changing parasitism rates overall. Although previous studies have shown variation in galler mortality components consistent with variation in gall size (van Hezewijk & Roland, ), we believe this to be one of the first demonstrations of competition from one guild of phytophagous insects resulting in an alteration of the parasitoid guild structure of another phytophagous species, mediated by host plant and by affecting gall size. The importance of accounting for plant‐trait‐mediated non‐trophic and indirect interactions has been emphasized by Ohgushi (), who demonstrated that including such interactions, which are common in natural communities and sometimes more common than direct trophic interactions, is essential for a complete understanding of factors affecting community composition and assembly.…”
Section: Discussionsupporting
confidence: 53%
“…Feeding niche (e.g., external feeder, leaf miner, leaf roller, or galler) could be an important factor affecting parasitoid community structure, because host insects with the same feeding niche have a similar parasitoid community (Askew and Shaw 1974, 1986, Pschorn-Walcher and Altenhofer 1989, Rott and Godfray 2000, Sugiura 2007, Bailey et al 2009). When insects share the same feeding niche, the feeding part of the plant (Hoffmeister 1992, Nyman et al 2007) and/or morphological traits of the feeding part (Hawkins and Goeden 1984, Van Hezewijk and Roland 2003, Salvo and Valladares 2004, Bailey et al 2009) also influence the parasitoid community structure. When insects share the same feeding niche, the feeding part of the plant (Hoffmeister 1992, Nyman et al 2007) and/or morphological traits of the feeding part (Hawkins and Goeden 1984, Van Hezewijk and Roland 2003, Salvo and Valladares 2004, Bailey et al 2009) also influence the parasitoid community structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the parasitoid community of leaf miners is characterized by the dominance of eulophid larval parasitoids (Hespenheide 1991, Kato 1996, Lewis et al 2002, that of lepidopteran gallers is characterized predominantly by parasitoids belonging to Eurytomidae, Torymidae, and Eupelmidae (Askew and Shaw 1986), and that of lepidopteran external feeders is characterized mainly by dipteran parasitoids in the family Tachinidae (Stireman and Singer 2003). When insects share the same feeding niche, the feeding part of the plant (Hoffmeister 1992, Nyman et al 2007) and/or morphological traits of the feeding part (Hawkins and Goeden 1984, Van Hezewijk and Roland 2003, Salvo and Valladares 2004, Bailey et al 2009) also influence the parasitoid community structure. In addition, previous studies have reported the influence of the host plant on parasitoid community structure: insect species using related host plants tended to share parasitoids or show similar parasitoid community structure (Askew and Shaw 1974, Hoffmeister 1992, Rott and Godfray 2000, Lill et al 2002, Bailey et al 2009, Leppa¨nen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Predation by birds has been investigated in the case of gall inducer species like Eurosta solidaginis [6], [7], Rabdophaga strobiloides [8], Giraudiella inclusa [9], Asteromya carbonifera [10]. In a recent study, Schönrogge et al quantified bird predation on invading insect galls [11].…”
Section: Introductionmentioning
confidence: 99%